(untitled) (Clinics, 2014)
OBJECTIVE: The aim of this placebo-controlled study was to evaluate the effects of pulsed and continuous ultrasound treatments combined with splint therapy on patients with mild and moderate idiopathic carpal tunnel syndrome. METHODS: The study included 46 carpal tunnel syndrome patients who were randomly divided into 3 groups. The first group (n = 15) received a 0 W/cm2 ultrasound treatment (placebo); the second group (n = 16) received a 1.0 W/cm2 continuous ultrasound treatment and the third group (n = 15) received a 1.0 W/cm2 1:4 pulsed ultrasound treatment 5 days a week for a total of 15 sessions. All patients also wore night splints during treatment period. Pre-treatment and post-treatment Visual Analogue Scale, Symptom Severity Scale and Functional Status Scale scores, median nerve motor conduction velocity and distal latency and sensory conduction velocities of the median nerve in the 2nd finger and palm were compared. Clinicaltrials.gov: NCT02054247. RESULTS: There were significant improvements in all groups in terms of the post-treatment Functional Status Scale score (p